Comparative study of the biological properties of Trypanosoma cruzi I genotypes in a murine experimental model (2015)
Chagas disease is an endemic zoonosis in Latin America and caused by the parasite Trypanosoma cruzi. This kinetoplastid displays remarkable genetic variability, allowing its classification into six Discrete Typing Units (DTUs) from TcI to TcVI. T. cruzi I presents the broadest geographical distribution in the continent and has been associated to severe forms of cardiomyopathies. Recently, a particular genotype associated to human infections has been reported and named as TcIDOM (previously named TcIa-b). This genotype shows to be clonal and adapted to the domestic cycle but so far no studies have determined the biological properties of domestic (TcIDOM) and sylvatic TcI strains (previously named TcIc-e). Hence, the aim of this study was to untangle the biological features of these genotypes in murine models. We infected ICR-CD1 mice with five TcI strains (two domestic, two sylvatic and one natural mixture) and determined the course of infection during 91days (acute and chronic phase of the disease) in terms of parasitemia, tissue tropism, immune response (IgG titers) and tissue invasion by means of histopathology studies. Statistically significant differences were observed in terms of parasitemia curves and prepatent period between domestic (TcIDOM) and sylvatic strains. There were no differences in terms of IgG antibodies response across the mice infected with the five strains. Regarding the histopathology, our results indicate that domestic strains present higher parasitemias and low levels of histopathological damage. In contrast, sylvatic strains showed lower parasitemias and high levels of histopathological damage. These results highlight the sympatric and behavioral differences of domestic and sylvatic TcI strains; the clinical and epidemiological implications are herein discussed. © 2014 Elsevier B.V.